Codon Optimized MMLV Reverse Transcriptase Expression and Functional Evaluation in Escherichia coli - Alfiyanti, Elsa; Andani Eka Putra; Rita Maliza; Alponsin, Alponsin (Jurnal Biologi Tropis, 2026)
Dependence on imported reverse transcriptase (RT) enzymes remains a challenge for the development of molecular diagnostic reagents, particularly in developing countries. This study aimed to design, express, purify, and functionally evaluate a recombinant Moloney Murine Leukemia Virus reverse transcriptase (MMLV-RT) as a candidate locally produced molecular biology reagent. A codon-optimized synthetic MMLV-RT gene was cloned into the pET-21a(+) expression vector and transformed into Escherichia coli BL21 (DE3). Recombinant protein expression was induced using IPTG, followed by purification using Ni²⁺-NTA affinity chromatography and characterization using SDS-PAGE. Functional activity of the recombinant enzyme was evaluated through reverse transcription of RNA templates followed by conventional PCR amplification. The optimized MMLV-RT gene was successfully expressed in E. coli BL21 (DE3), producing a recombinant protein band at approximately 55.4 kDa. The highest protein yield was obtained after overnight induction, reaching 3.385 mg/mL. Purification resulted in a dominant protein band corresponding to the expected molecular weight of MMLV-RT. Functional evaluation demonstrated that recombinant MMLV-RT successfully generated specific PCR amplicons with performance comparable to commercial reverse transcriptase without detectable non-specific amplification. These findings indicate that recombinant MMLV-RT produced in E. coli BL21 (DE3) retains functional reverse transcriptase activity and has potential for further development as an alternative locally produced reagent for molecular diagnostic applications.